A Pilot Study of Anti-CTLA4 Antibody Ipilimumab in Patients with Synovial Sarcoma. (11th March 2013) - Maki, Robert G.; Jungbluth, Achim A.; Gnjatic, Sacha; Schwartz, Gary K.; D'Adamo, David R.; Keohan, Mary Louise; Wagner, Michael J.; Scheu, Kelly; Chiu, Rita; Ritter, Erika; Kachel, Jennifer; Lowy, Israel; et al.
Abstract : Background . Patients with recurrent synovial sarcomas have few options for systemic therapy. Since they express large amounts of endogenous CT (cancer testis) antigens such as NY-ESO-1, we investigated the clinical activity of single agent anti-CTLA4 antibody ipilimumab in patients with advanced or metastatic synovial sarcoma. Methods . A Simon two-stage phase II design was used to determine if there was sufficient activity to pursue further. The primary endpoint was tumor response rate by RECIST 1.0. Patients were treated with ipilimumab 3 mg/kg intravenously every 3 weeks for three cycles and then restaged. Retreatment was possible for patients receiving an extra three-week break from therapy. Sera and peripheral blood mononuclear cells were collected before and during therapy to assess NY-ESO-1-specific immunity. Results . Six patients were enrolled and received 1–3 cycles of ipilimumab. All patients showed clinical or radiological evidence of disease progression after no more than three cycles of therapy, for a RECIST response rate of 0%. The study was stopped for slow accrual, lack of activity, and lack of immune response. There was no evidence of clinically significant either serologic or delayed type hypersensitivity responses to NY-ESO-1 before or after therapy. Conclusion . Despite high expression of CT antigens by synovial sarcomas of patients treated in this study, there was neither clinical benefit nor evidence of anti-CT antigen serological responses. Assessment of the ability of synovial sarcoma cell lines to present cancer-germ cell antigens may be useful in determining the reason for the observed lack of immunological or clinical activity.